Implementasi Inovasi Sekunder dan Penguatan Kapasitas Produksi Kopi Robusta melalui Transfer Teknologi dan Hibah Alat di Desa Gunungjaya, Salem, Brebes - Sugeng Rianto; Sutarmin Sutarmin; Undri Rastuti; Mia Anjani; Tria Putri Yani; Meri Aguk Setiani; M. Hari Ramadhan (Pusat Riset dan Inovasi Nasional, 2025)
Salem District is one of the largest coffee commodities in Brebes Regency. This significant potential has yet to provide a meaningful contribution to the income of coffee farmers, especially in Gunung Jaya village, Salem District. The low income of coffee farmers is due to the fact that they still sell their coffee products in the form of cherry. Over time, in 2018, farmers began to develop small-scale and simple coffee processing from green beans to roasted beans and coffee powder, pioneered by the SME